Exploring the pathogenesis of age-related macular degeneration: A review of the interplay between retinal pigment epithelium dysfunction and the innate immune system - Wong, Josephine H. C.; Ma, Jessica Y. W.; Jobling, Andrew I.; Brandli, Alice; Greferath, Ursula; Fletcher, Erica L.; Vessey, Kirstan A. (Frontiers in Neuroscience, 2022)
Age-related macular degeneration (AMD) is a leading cause of irreversible vision loss in the older population. Classical hallmarks of early and intermediate AMD are accumulation of drusen, a waste deposit formed under the retina, and pigmentary abnormalities in the retinal pigment epithelium (RPE). When the disease progresses into late AMD, vision is affected due to death of the RPE and the light-sensitive photoreceptors. The RPE is essential to the health of the retina as it forms the outer blood-retinal barrier (BRB), which establishes ocular immune regulation, and provides support for the photoreceptors. Due to its unique anatomical position, the RPE can communicate with the retinal environment and the systemic immune environment. In AMD, RPE dysfunction and the accumulation of drusen drives the infiltration of retinal and systemic innate immune cells into the outer retina. While recruited endogenous or systemic mononuclear phagocytes (MPs) contribute to the removal of noxious debris, the accumulation of MPs can also result in chronic inflammation and contribute to AMD progression. In addition, direct communication and indirect molecular signalling between MPs and the RPE may promote RPE cell death, choroidal neovascularization and fibrotic scarring that occurs in late AMD. In this review, we explore how the RPE and innate immune cells maintain retinal homeostasis, and detail how RPE dysfunction and aberrant immune cell recruitment contributes to AMD pathogenesis. Evidence from AMD patients will be discussed in conjunction with data from preclinical models, to shed light on future therapeutic targets for the treatment of AMD.